Impact of vertebral derotation on ventilatory function and chest circumference in adolescent scoliosis - Takey Ahmed, Khaled; Mohamed Hamed, Abla; Helmy, Akram M.; Mohamed, Walaa Mohsen; Bahey El-Deen, Heba A.; El Hawary, Youssry (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Scoliosis has been associated with thoracic cavity alterations that impair pulmonary function. Correcting sco-liotic deformity regains normal pulmonary function by maintaining respiratory and muscular eﬃciency. This study aims to com-pare pulmonary function and thoracic volume at baseline and after correcting the scoliosis deformity.Methods. A total of 56 patients, 46 girls and 10 boys, were diagnosed with idiopathic scoliosis. Participants were randomly allocated into two equal groups. Group A was treated with posterior correction, vertebral derotation, and a pulmonary rehabilita-tion program, while group B was treated with the same treatment given to group A without derotation. Evaluation of the measur-ing variables was carried out pre-operatively, immediately post-operatively, and three months after the operation. In addition, post-operatively, participants were treated with segmental breathing exercise training and incentive spirometry, 3 sessions per week for 3 months.Results. A signiﬁcant reduction in the Cobb angles, angles of rotation, and chest expansion was observed in both groups by comparing both initial and post-operative mean values, while a signiﬁcant reduction was revealed in group A (p = 0.0001). The mean values of FEV1 and MVV immediately post-operatively showed a signiﬁcant reduction in both groups, which was highly signiﬁcant for group A. At three months post-operatively, both groups showed highly signiﬁcant improvement (p = 0.001).Conclusions. In addition to its beneﬁcial eﬀects on curve correction and the angle of rotation, the vertebral derotation tech-nique impairs physiological and mechanical parameters immediately post-operatively. However, a beneﬁcial eﬀect was detected after three months of pulmonary rehabilitation in all parameters.
Keywords: adolescent idiopathic scoliosis; vertebral derotation; pulmonary function test; angle of rotation; chest circumference